Heat source recognition sensor mimicking the thermosensation function of human skin - Wenting Sun; Pengxiang Zhang; Xinyi Lin; Yupeng Wang; Shuaihua Wang; Bin Yang; Zijian Zheng; Weishu Liu (The Innovation, 2024)
Summary: The human skin maintains a comfortable and healthy somatosensory state by sensing different aspects of the thermal environment, including temperature value, heat source, energy level, and duration. However, state-of-the-art thermosensors only measure basic temperature values, not the full range of the thermosensation function of human skin. Here, we propose a heat source recognition (hsr) sensor of poly(butyl acrylate)-lithium bis(n-fluoroalkylsulfonyl)imide (PBA-Li:nFSI; n = 1, 3, 5), which enables response to temperature, pressure, and proximity stimulus signals based on the relaxation behavior of the ionic gel and distinguished between different types of heat sources (i.e., radiation, convection, and conduction). The hsr sensor was integrated into a prosthetic limb covered by an e-skin with isothermal regulation, and experiments with a robot showed that it could achieve human-like thermosensation function, recognizing multidimensional information about thermal environments, such as temperature value, comfort level, and heat source signal. This work deeply mimics the human body’s thermosensation function and provides a reliable solution for the development of bionic e-skin for intelligent robots and prosthetics.